EFFECTIVENESS THE SAVER OF ASI ON COLD TEMPERATURE 0-10oC BETWEEN ROOM TEMPERATURE 19oC-26oC CONTENS STANDARD LACTOSE IN VILLAGE WANGLUTRUCUK KLATEN, - Rani Novita Sari; Kuswati .; Witriyani . (STIKES DUTAGAMA KLATEN, 2015)
Background : The result of research the ASI gift shown 37,18% from 488.495 just 181.600 the baby that have exclusive ASI from the mother because she is busy to work and they choose formula milk. In indonesia on 2012 years day by day the growth of technology, woman carier more to choice ASI that she squeeze for her baby it saves in the cold temperature and room temperature it make the baby stillto drink withexclusive program. Purpose : The purpose of research is knowing the effectiveness from the saver of ASI on cold temperature 0-10oC between room temperature 19oC-26oC contens standard lactose. Methods : The research used methods true experiment with pretest-posttest. The sample interpretation is Quota Sampling. The data was analyzed by using Chi Square test and processed with SPSS release 16.0. Result : The Research sample of 30 bottle ASI in measure contens standard lactose as pretest with result effective of 15 sample (100%) in cold temperature and room temperature effective of 13 sample (86%) and posttest with result in the cold temperature effective of 13 sample (86%) and in the room temperature effective 3 sample (20%). Conclusion : The saves of ASI on cold temperature 0-10oC more than effective in between room temperature 19oC-26oC contens standard lactose.